СМАРТ (SMAPT) -цели и критерии успешности при формативном оценивании - Калиева, К.Т. (My University, 2016)
In article use of the smart purposes, a smart - criteria is considered at a formative assessment . Actuality consists in that the problem of purposeful activity of man always remains actual, that is why as without an aim there is not a management and there is not a result. The main task of teacher consists of that it is methodically correct to set forth the aim of lesson and project facilities of her achievement at educating. The training of the pupil , controlled and operated by a teacher, is carried out in the process of evaluation. Study of process evaluation of activity of students showed that an evaluation process carried arbitrary character how clear, scientifically adjusted positions teachers would that follow are absent. Therefore an evaluation is one of features of the updated curriculum of secondary education in the Republic of Kazakhstan. A research aim is the detailed study of methodology of SMART and analysis of her efficiency in practice. An author underlines importance of understanding students that is considered success at educating and it plugs in itself the acquaintance of their with aims, tasks and success criteria of education. If students under take more responsibility for the own educating, they must know that it is gathered to study, that is successful educating and as they can understand, that succeeded.
Keywords: smart goal; Smart criteria; formative assessment; goal-setting; competence-based approach